Tsunami: the world’s greatest waves, by James Goff and Walter Dudley, 2021. Oxford University Press, USA, 231 pages. Hardback: price 17.24, ISBN 0197546129 - Pleskot, Krzysztof (Geologos, 2022)
No abstract available.